STRATEGI PEMERTAHANAN BAHASA JAWA DI PROVINSI DAERAH ISTIMEWA YOGYAKARTA - Endang Nurhayati (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2013)
This study aims to describe the factors causing the Javanese language use shift and the maintenance strategies and attempts. It employed the qualitative approach with a focus on the mapping of maintenance models in the Province of Yogyakarta Special Territory. The findings are as follows. First, the factors causing the shift include: (a) perceptions of the Javanese language, (b) complexity of societal life, (c) the number of Javanese speakers, and (d) the use of Javanese in the family. Second, the attempts made include: (a) the strengthening of the philosophy of the Javanese culture and language, (b) the Javanese language competitions and festivals, (c) the dissemination of moral values in Javanese expressions, (d) the development of Javanese performance arts, and (e) the use of Javanese in institutions. Third, the maintenance strategies include the uses of Javanese as: (a) a means of communication, (b) a factor uniting language and culture, (c) a local wisdom, (d) a local government’s policy, (e) a subject in education, (g) NGO activities,and (h) Javanese journalism.